Avaliação de risco precoce do Jaburetox: um peptídeo inseticida derivado da urease de Canavalia ensiformis com fins de aplicação biotecnológica - Sá, Chayenne Alves de (2018)
Jaburetox (JBTX) is a peptide derived from a Canavalia ensiformis urease isoform which exhibits potent insecticidal activity, and therefore it has been considered a promising candidate for development of genetically modified (GM) crops. However, to ensure the safe use of transgenic cultures expressing new exogenous peptides and proteins, food safety tests have to be performed to identify risks associated to these bioactive molecules. Among the most used approaches to evaluate the risk of recombinant proteins, the two-tiered weight-of- evidence method proposed by the International Life Sciences Institute (ILSI) has been widely accepted. This approach stands out from the others by taking into account the analysis of the data obtained in a holistic way. The stage I consists of: 1. History of safe use research; 2. Bioinformatics analysis; 3. Mode of action and protein specificity; 4. In vitro digestibility analysis and temperature stability tests; and, 5. Safe estimation of the levels of expression and dietary intake of the processed grains. In the stage II, a case-by-case study is recommended for each protein. In addition to this approach, our group has also proposed that the safety assessment of new proteins be performed precociously inside of the transgenic production chain. Thus, the safety evaluation is no longer carried out after the development of the transgenic but in the stages of prospecting and characterization of the new protein, which effectively can detect antinutritional, toxic and/or allergenic properties and, therefore, lead to decisions such as the exclusion of the protein from a potential biotechnological application or to promote structural modifications. In this context, this study aimed to perform the early risk assessment of the insecticidal peptide JBTX, its parental protein, the urease of C. ensiformis (JBU), and the JBURE II urease isoform. For that, the ILSI approach was used, with some modifications. From this research, C. ensiformis species, JBU and its derivative proteins have shown a history of safe use; the JBTX peptide did not show significant similarity of its primary amino acid sequence with allergenic, toxic and/or antinutritional proteins; this peptide showed to have mode of action little understood, however, it presented high specificity against insects. Based on these results, it was possible to conclude that no risk associated with the consumption of this peptide is expected.